ANALISIS PEMBIAYAAN MURABAHAH DI BMT AMANAH UMMAH SUKODONO - Indah Ajeng Pratiwi Ate; Dewi Riza Lisvi Vahlevi (ICO EDUSHA, 2021)
This study aims to determine and analyze murabahah financing at BMT Amanah Ummah Sukodono. Murabaha financing still dominates the composition of financing in Islamic financial institutions, including BMT. BMT assesses that the murabahah financing process has a small risk so that BMT spends more on this type of financing. The composition of murabahah financing which is still very large in BMT and the existence of muamalah rules which state that "profit is a reward for being prepared to bear losses" poses the risk of murabahah financing, the management process since the prospective member or member of the BMT proposes financing until the repayment of financing installments is interesting to study. This study uses a qualitative approach. Primary data comes from interviews with BMT administrators and managers, participatory observations, and focus group discussions (FGD) as well as documents related to murabahah financing. Secondary data comes from books, journals, magazines, newspapers, and documents or reports on research activities that have been carried out related to financing in the BMT Amanah Ummah. This research concludes that:1) Murabahah Financing is the principle of buying and selling where the selling price consists of the cost price plus the profit value that has been agreed between the two parties.2) Factors that cause financing problems are due to the Customer himself and the BMT Amanah Ummah Sukodono not understanding the character of the members, the poor economic conditions and business development and the BMT Amanah Ummah being less careful and thorough in analyzing the data of prospective customers.3) To deal with problematic financing in murabahah contracts, BMT Amanah Ummah Sukodono uses a family system by approaching problem customers. Keywords : Murabahah Financing, BMT, Problem financing factor, customer References Antonio, Muhammad Syafii. (2005). Bank Syariah dari Teori ke Praktik. Jakarta: Gema Insani. Baitul Maal Muammalat. Tanpa Tahun. Tata Cara Pendirian BMT, (Online) (http://baitulmaal.net/downlot.php?file=files/Tata_Cara_Pendir ian_BMT.pdf Janwari, Yadi. 2015. Lembaga Keuangan Syariah. Bandung: PT Remaja Rosdakarya. Joko Subagyo. Metodologi Penelitian Teori dan Praktek (Jakarta : PT. Rineka Cipta, 2004) hal.39 Mardani. 2015. Aspek Hukum Lembaga Keuangan Syariah di Indonesia. Jakarta: Prenadamedia Group. Moleong, Lexy J. 2017. Metodelogi Penelitian Kualitatif. Bandung : PT. Remaja Rosdakarya. Permodalan BMT. (2009). (http://permodalanbmt.com/?p=70 Rizki,Muhammad 2014, analisis faktor-faktor yang mempengaruhi terjadinya resiko pada pembiayaan murabahab BMT Amanah Ummah Sidoarjo,Skripsi, Ubaya, Surabaya, Suharsimi Arikunto, Prosedur Penelitian: Suatu Pendekatan Praktik, (Jakarta: Rineka Cipta, 1998) hal 234 System dan prosedur, KJKS BMT Amanah Ummah Kc. Karah agung Surabaya :2015 Ubaidillah. 2018. “Pembiayaan Bermasalah pada Bank Syariah: Strategi Penanganan dan Penyelesaiannya.” el-JIZYA, Jurnal Ekonomi Islam, Vol. 6, No. 2 Wawancara dengan bu titik, manager BMT Amanah Ummah Kc. Sukodono 2021 Wawancara dengan teller dan admin BMT Amanah Ummah Kc. Sukodono 2021 Wawanvara dengan bapak suliyantoro manager pusat BMT Amanah Ummah Surabaya 2021 Website resmi BMT Amanah Ummah Sukodono WWW.BMTAMANAHUMMAH.COM